Love for Diversity: An Insect Community Study on Turnera sp. at the Perbaungan Oil Palm Plantation for the Development of Animal Ecology Teaching Materials - Mariana Ritonga; Edi Azwar; Sularno Sularno (Mahesa Research Center, 2026)
This study aims to analyze the diversity of insects in the eight-o'clock flowering plant (Turnera sp.) at PTPN IV Adolina Perbaungan Garden and compile the results as teaching materials for Animal Ecology in the form of a monograph book. The study used a quantitative descriptive method with purposive sampling techniques at three observation stations representing microhabitat variations. Data collection was carried out through direct observation, insect capture using sweeping nets and hand picking, morphological identification, and air temperature and humidity measurements. The results of the study found 356 individual insects consisting of 21 species, 5 orders (Hymenoptera, Lepidoptera, Diptera, Coleoptera, and Hemiptera), and 16 families. The value of the Shannon-Wiener diversity index (H') ranges from 1.1395-1.1547 (medium category), the Pielou uniformity index (E) ranges from 0.3870-0.3995 (low category), and the Simpson dominance index (C) ranges from 0.0830-0.0919 (low category). The pollinator group dominated the community with 215 individuals (60.39%). The results of the research were compiled into a monograph book containing species identification, morphological characteristics, visual documentation, ecological roles, and analysis of community structure as a contextual learning resource in the Animal Ecology course.